Prevention Interventions for People Living with HIV in Military Settings - P. Grillo, Michael; Sloan, Margo; Wankie, Che; Woodland, Kelly; Reader, Elizabeth; Porter, Bruce; A. Macera, Caroline; A. Shaffer, Richard (Current HIV Research, 2017)
Background: Military HIV prevention programs and healthy living programs were developed in the mid-1980s to manage and support newly HIV-positive military personnel in the US military. Since then, a program developed by the Centers for Disease Control and Prevention with support from the Department of Defense HIV/AIDS Prevention Program (DHAPP), called Positive Health, Dignity and Prevention (PHDP), is currently being rolled out by DHAPP in partner militaries. The program, designed to reduce HIV transmission, is a package of interventions for people living with HIV (PLHIV), including risk reduction counseling, condom provision, disclosure counseling, testing of sexual partner(s) and children, adherence counseling, diagnosis and treatment of sexually transmitted infections, and provision of family planning services. Methods: DHAPP has trained military and civilian personnel caring for military personnel, their families, and the civilians seen at military installations in sub-Saharan Africa, such as Rwanda, Democratic Republic of the Congo, Malawi, and Zambia. These programs have varying degrees of implementing the program with innovative ways of engaging PLHIV. Results/Conclusions: Many successes are being achieved through the training of military and civilian personnel working for or at military health care settings. In 2015, one of DHAPP's goals for the PHDP program is to enhance the monitoring, evaluation, and reporting of PHDP to demonstrate PHDP service provision to at least 90% of HIV-positive patients over the next 5 years.
Keywords: PEPFAR